Les théories de la gouvernance. Pluralité de discours et enjeux éthiques - Alain Létourneau (VertigO)
Reflexion on the governance topic and the different uses of that term are going forward in the field of environmental issues and practices. Since that topic is very popular, we suppose it can only grow in the upcoming years. Considering it might be too soon to produce at this time a typology of governance theories or a too strict conceptualisation of the notion, we aim here instead at identifying the different ways in which this term is used in a plurality of discourses and how it probably goes with a plurality of meanings. We are at the starting point of field studies on governance practices; it seems more interesting now to focus on how the concept actually works in practice, instead of trying to build a unifying model from the theoretical point of view. A purely theoretical endeavour would probably miss the various ways by which actors find and give meaning to the uses of the governance concept. We also would like to reflect on the effects produced by uses of governance and what are the ethical issues that are raised by these uses.